UMP, Malaysian Cocoa Board collaboration strengthens efforts on Malaysian cocoa industry development - Mimi Rabita, Abdul Wahit (2021)
KUALA LUMPUR, 22 April 2021 - Universiti Malaysia Pahang (UMP) and the Malaysian Cocoa Board (MCB) will conduct research on producing cocoa extract, developing healthcare products based on cocoa extract and developing e-Nose sensor technology that uses artificial intelligence system to improve cocoa bean quality inspection.